2013
DOI: 10.1371/journal.pone.0072069
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Oxidative Stress Markers in Women with Uterine Leiomyoma

Abstract: BackgroundUterine leiomyomas (fibroids) are the most common gynaecological benign tumors in premenopausal women. Evidences support the role of oxidative stress in the development of uterine leiomyoma. We have analysed oxidative stress markers (thiols, advanced oxidized protein products (AOPP), protein carbonyls and nitrates/nitrites) in preoperative sera from women with histologically proven uterine leiomyoma.Methodology/Principal FindingsWe conducted a laboratory study in a tertiary-care university hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 55 publications
5
23
1
1
Order By: Relevance
“…Uterine fibroids are very common gynecological pathologies and have been tried to be associated with oxidative pathways (26). Individuals with uterine fibroids were found to have lower serum thiol levels and higher oxidative protein products compared to individuals in the control group (27). Similar results have been shown in different studies and it has been shown that both oxidative and antioxidative capacities are increased (28).…”
Section: Inhibition Of Oxidative Stress In the Cell By Amino Acids Ansupporting
confidence: 84%
“…Uterine fibroids are very common gynecological pathologies and have been tried to be associated with oxidative pathways (26). Individuals with uterine fibroids were found to have lower serum thiol levels and higher oxidative protein products compared to individuals in the control group (27). Similar results have been shown in different studies and it has been shown that both oxidative and antioxidative capacities are increased (28).…”
Section: Inhibition Of Oxidative Stress In the Cell By Amino Acids Ansupporting
confidence: 84%
“…In humans, AOPP increase has been associated with several immuno-inflammatory markers and they have been proposed as an exquisite marker of OS correlating with monocyte activation (Witko-Sarsat et al 1998). The prolonged half-life of AOPP allows an indirect reflection of the intensity of the OS (Santulli et al 2013) and has been reported to be elevated in dairy cows with embryonic mortality (Celi et al 2011). The AOPP level was elevated at 9 h and this may have been associated with the development of the cyst in cow 1258; however, this cannot be concluded definitively from the results of this study.…”
contrasting
confidence: 52%
“…Previous studies showed that multiple oxidative stress biomarkers, such as NOX4 ( 16 ), 8-OH-dG ( 17 ), and malonaldehyde ( 44 ), as well as serum oxidative stress markers ( 45 ), are increased in ULM. Moreover, unlike immortalized MM cells, activity of both catalase and extracellular SOD3 is significantly reduced in immortalized ULM cells ( 46 ).…”
Section: Discussionmentioning
confidence: 99%